The risk of public mobility from hotspots of COVID-19 during travel restriction in Bangladesh - Probir Ghosh; Mohammad Manir Mollah (Journal of Infection in Developing Countries)
Bangladesh reported the first three laboratory-confirmed COVID-19 cases on March 8, 2020 in Dhaka and Narayanganj cities. As of April 8, 2020, 218 confirmed cases across the country, they have mostly detected from Dhaka (56.4%) and Narayanganj (21%) cities where the hotspots of an outbreak of COVID-19 disease. There were 6 cases in Dhaka district excluding metropolitan areas and rest of 43 (20%) cases in the 19 other regions. Local government-enforced completely shut down the hotspots areas on April 8 2020. However, peoples from hotspots travelled openly to the other districts.